2021
DOI: 10.3390/jcm10071488
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Periodontitis: The Most Promising Salivary Biomarkers for Early Diagnosis of Periodontitis

Abstract: The primary cause of tooth loss in the industrialized world is periodontitis, a bacterial anaerobic infection whose pathogenesis is characterized by composite immune response. At present, the diagnose of periodontitis is made by a complete status check of the patient’s periodontal health; full-mouth plaque score, full-mouth bleeding score, probing depth, clinical attachment level, bleeding on probing, recessions, mobility, and migration are evaluated in order to provides a clear picture of the periodontal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 103 publications
(140 reference statements)
1
37
0
Order By: Relevance
“…Periodontal disease is one of the more common inflammatory diseases in the adult population, with an incidence varying from 5 to 30% [ 1 , 2 , 3 , 4 ]. Periodontal disease, initiated by bacterial biofilms, can cause the destruction of soft and hard periodontal tissues, consequently leading to tooth loss [ 5 , 6 , 7 ]. Periodontal disease produces inflammatory mediators and microbial products that can enter the systemic circulation through the mouth and reach distant organs [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontal disease is one of the more common inflammatory diseases in the adult population, with an incidence varying from 5 to 30% [ 1 , 2 , 3 , 4 ]. Periodontal disease, initiated by bacterial biofilms, can cause the destruction of soft and hard periodontal tissues, consequently leading to tooth loss [ 5 , 6 , 7 ]. Periodontal disease produces inflammatory mediators and microbial products that can enter the systemic circulation through the mouth and reach distant organs [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal disease produces inflammatory mediators and microbial products that can enter the systemic circulation through the mouth and reach distant organs [ 8 , 9 ]. Indeed, several studies have shown a link between periodontal disease and some frequent systemic pathologies [ 10 ] such as diabetes [ 11 ], cardiovascular disease [ 12 , 13 ], respiratory disease [ 14 ], obesity [ 15 ], cancer [ 16 , 17 ], and preterm birth (PTB) [ 7 ]. Vitamin D is a secosteroid that can be ascribed to steroid hormones if considering its biological effects on several tissues [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The differential microbial species and metabolites in the GCF among those with periodontal pathology and healthy subjects are potential biological indicators, indicating a possible approach to forecast, diagnose, and accomplish individualized periodontal treatment [ 133 , 134 , 135 , 136 ]. Periodontal pathology is related to misbalanced homeostasis in the oral tissues, microbial progression, and development of the dental biofilm on the dental prostheses.…”
Section: Bacteriological Evaluation Following Dental Prosthesesmentioning
confidence: 99%
“…Importantly, this succession from facultative to more anaerobe species is finally accountable for gingivitis and periodontitis etiology [10,71,77,79]. Periodontitis is a chronic inflammatory disease that can lead to non-reversible damage of supportive tissues (cementum, periodontal ligament, and alveolar bone) surrounding the teeth and tooth loss [80,81]. Mechanistically, the increased concentration of pathogenic bacteria (dysbiosis) within the dental plaque activates a massive deleterious immune response [82].…”
Section: Oral Dysbiosismentioning
confidence: 99%